Induction of Resistance Against Plutella xylostella (L.) (Lep.: Plutellidae) by Jasmonic Acid and Mealy Cabbage Aphid Feeding in Brassica napus L. - Nouri-Ganbalani, Gadir; Borzoui, Ehsan; Shahnavazi, Maryam; Nouri, Alireza (Frontiers in Physiology, 2018)
The diamondback moth, Plutella xylostella (L.), has become the most destructive insect pest of cruciferous plants, such as B. napus throughout the world including Iran. In this study, the induction of resistance was activated in oilseed rape plants (Brassica napus L.) using foliar application of jasmonic acid (JA) and mealy cabbage aphid either individually or in combination against diamondback moth. Induced resistance by inducers significantly reduced the population growth parameters, as well as the survival rate of immature P. xylostella. Also, the nutritional indices of P. xylostella were studied to evaluate the potential impact of induced resistance on the insect feeding behavior. The values of the efficiency of conversion of ingested food (ECI), the efficiency of conversion of digested food (ECD), relative consumption rate (RCR), and relative growth rate (RGR) of P. xylostella on JA-treated plants were significantly reduced compared to control. These are because glucosinolates and proteinase inhibitors (PIs) are induced following treatment of plants. Also, we found a significantly higher GOX activity in the salivary gland extracts of larvae fed on JA treatment. These results express that JA and/or Aphid application induces systemic defenses in oilseed rape that have a negative effect on P. xylostella fitness. These findings develop our knowledge the effects of induced defenses on P. xylostella.